The relationship between society and language acquisition: influence and interaction, a comparative study between linguistics, sociology, and philosophy - Mahmoud, Omar Nihad (Edelweiss Applied Science and Technology, 2024)
Language is one of the most significant aspects of human behavior, serving as a tool to express thoughts and emotions while also revealing societal identity and culture. This importance has attracted the attention of linguists, psychologists, sociologists, and other scholars to study language and its impact on humans. Language plays a pivotal role in maintaining societal cohesion and unity by acting as a binding medium across generations. However, disruptions to this tool pose challenges to linguistic communication within society, as it serves as the foundation for interaction and engagement. Based on this understanding, sociologists and cultural scholars have emphasized the importance of the first language, focusing on its transmission to future generations and its development through raising awareness and educating members of society. The primary aim of this paper is to provide an accurate description of the relationship between society, environment, and language. Raised in a culturally deprived environment, a person often experiences linguistic disadvantage, as the linguistic development of any society, across all its dimensions and aspects, significantly impacts its members. Given that the study uses Arabic as a model to present its ideas, it seeks to establish the connection between language and identity in general and Arabic specifically. Society regards Arabic as an essential component and dynamic factor. Identity has emerged as a critical issue on the international stage, particularly after the transformations that have reshaped the structure of the global system.